Penguatan Pendidikan Karakter Berbasis Multikultural melalui Mata Pelajaran PKn - Bakar, Abu (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This study aims to analyze the strengthening of multicultural-based character education through Civics (PKn) subjects in Islamic Elementary Schools (MI) by employing a qualitative library research method. The research subjects consist of academic literature, including books, journals, and policy documents, while the object of study focuses on the integration of multicultural values in the PKn curriculum at the MI level. Data were collected through systematic searches in academic databases using keywords such as